Association Between Visit‐to‐Visit Blood Pressure Variability and Incidence of Atrial Fibrillation in Hypertensive Patients: A Post‐Hoc Analysis of the SPRINT Trial - Guixin Liu; Ning Wang; Keyang Zheng; Wenli Cheng (The Journal of Clinical Hypertension)
ABSTRACT Visit‐to‐visit blood pressure variability (BPV) has been recognized as a cardiovascular risk factor, but its association with new‐onset atrial fibrillation (AF) remains underexplored. This study investigated the relationship between BPV and AF incidence among hypertensive patients using data from the Systolic Blood Pressure Intervention Trial (SPRINT). Visit‐to‐visit BPV was quantified using standard deviation (SD), coefficient of variation (CV), and average real variability (ARV) of systolic and diastolic blood pressure measurements. Participants were stratified into three groups based on systolic BPV tertiles. AF cases were identified via follow‐up electrocardiograms and reports of AF‐related serious adverse events. After excluding individuals with baseline AF or missing BPV data, 7378 patients were analyzed over a median follow‐up of 3.8 years. The incidence of new‐onset AF increased across ascending tertiles of systolic BPV (CV), with rates of 2.5% (62 cases), 4.1% (104 cases), and 5.2% (127 cases) observed in the lowest to highest tertiles, respectively. After adjusting for age, race, blood pressure, and cardiovascular risk factors, the hazard ratios for AF in the second and third tertiles compared to the lowest tertile were 1.52 (95% CI: 1.10–2.09) and 1.83 (95% CI: 1.34–2.49), respectively. Consistent trends were noted for systolic BPV measured via SD and ARV, as well as diastolic BPV. These findings indicate that elevated visit‐to‐visit BPV independently predicts AF development in hypertensive populations. Assessing BPV may enhance risk stratification and identify patients at heightened risk for AF, underscoring its clinical relevance in hypertension management.